Postharvest quality of guava with a novel gum Arabic-beeswax-coconut oil coating under ambient and chilling storage - Ung Hua Ting; Mohd Zahid bin Abidin; Francis Yew Fu Tieng; Mohd Syafiq bin Abdullah; Armstrong Ighodalo Omoregie; Abdul Fattah B. Ab Razak; Mohammad Hafsanjani bin Salleh; Siti Nadhira binti Mohamad Basri (Journal of the Saudi Society of Agricultural Sciences)
Abstract Postharvest losses of tropical fruits like guava remain a significant challenge, with traditional preservation methods often proving ineffective. This study investigates a novel composite edible coating made from gum Arabic, beeswax, and coconut oil to extend the shelf life and preserve the quality of guava (cv. Cambodia). While edible coatings have been widely studied, limited research exists on this specific formulation for guavas. Briefly, guavas were treated with the coating and stored under ambient and chilling (12–13 °C, 50–60% RH) conditions. Key parameters, including weight loss, firmness, titratable acidity (TA), total soluble solids (TSS), and sensory attributes, were analysed. Results showed that the uncoated guavas stored under the ambient conditions experienced the highest weight loss (17.43%) by the 7th day, while they maintained quality until the 15th day under the chilling conditions. Coated chilled guavas achieved the longest postharvest shelf life of 35 to 40 days and they demonstrated superior performance, retaining firmness (1192.30 g), and exhibiting slower increments in TSS (10.67°Brix) and TA (0.79%). Sensory evaluations further highlighted the coating's effectiveness, with improved appearance and acceptability in coated samples. In conclusion, the gum Arabic-beeswax-coconut oil coating effectively extends guava shelf life, presenting a promising strategy for reducing postharvest losses in tropical fruits. Future research should focus on optimising the coating's composition for scalability and assessing its compatibility with different fruit varieties under varying storage conditions.